Development of object-oriented components for atm network simulation with emphasis on schedule policies in traffic shaping / Wong Chee Sum - Wong, Chee Sum (2001)
Asynchronous Transfer Mode (ATM) is considered to be the ground which B-ISDN is to be built. The traffic control of ATM network is important to provide Quality of Service (QoS) for network applications Therefore, different traffic management procedures have been introduced to achieve network performance objectives. Traffic shaping is one of the traffic management mechanisms that able to protect the network and the end-system from congestion probleam. This project focuses on the development for simulation of different scheduling policies in traffic shaping with object-oriented approach. The simulator is designed and implemented to ensure the correctness of scheduling within the network nodes, fairness of scheduling and to guarantee quality of service for ATM application. Simulation modeling is an ideal domain for the application of object-oriented methods, both in the modeling of problem domain entities and in the implementation of simulators. A development of an object-oriented, platform independent, web-enabled, and multithread discrete-event simulator will build using Java programming language.